STRATEGI PERBAIKAN SISTEM AGROFORESTRI DAN KONSERVASI LAHAN DI DESA PONDOKAGUNG, KECAMATAN KASEMBON, KABUPATEN MALANG - Arif Cahyo Wibowo, Febri; Triwanto, Joko; Tri Kurniawan, Edwin; Muttaqin, Tatag (Wahana Forestra: Jurnal Kehutanan, 2020)
Production forest area in Pondokagung village needs agroforestry system to meet economic needs and as buffer against natural disasters such as erosion. Research conducted on agroforestry land was carried out to determine agroforestry management as conservation system. Research was conducted in June-August 2019 using data collection methods in the form of land slope measurement, long slope, soil sampling. Retrieve secondary data for monthly rainfall data for 2017-2019 and related studies. Results obtained in agroforestry area had an erosion value in 2018 with a value of 112.19 tons/ ha/year and the slope class agreed to III and II. The area of ​​agroforestry land is removed by mahogany vegetation in SPL 3, while in SPL 1 and 2 it is mountain spruce and SPL 4 area is in mixed form. The level of erosion hazard posed to agroforestry land in location is relative from year to year, so the effect of agroforestry conservation is very good in area are needed that can increase the danger of erosion. Soil fertility conditions in agroforestry land are low with a C-organic content value (0.78%) containing alluvial and podsolic soils with a yellowish red color. The action taken is vegetative conservation techniques, mechanical and tillage